Titanium superoxide: a heterogeneous catalyst for anti-Markovnikov aminobromination of olefins - Shaikh, Tanveer Mahamadali; Karabal, Pratibha U.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2009)
A new facile procedure for the aminobromination of olefins in high yields has been described using p-toluene sulfonamide (p-TsNH(2)) and N-bromosuccinimide (NBS) as introgen and bromine sources, respectively, and titanium superoxide as a truly heterogeneous catalyst. The formation of anti-Markovnikov product exclusively in all the cases studied possibly proceeding I free radical reaction pathway is remarkable. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: anti-Markovnikov addition; Bromoamination; N-Bromosuccinimide; p-Toluenesulfonamide; Titanium superoxide

NaIO4/LiBr-mediated aziridination of olefins using chloramine-T - Karabal, Pratibha U.; Chouthaiwale, Pandurang V.; Shaikh, Tanveer M.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2010)
A new milder protocol for aziridination of a variety of olefins has been described. The process employs catalytic amount of sodium metaperiodate (NaIO4) as an oxidant and LiBr and chloramine-T as the bromine and nitrogen sources, respectively. Interestingly, the formation of aziridine products in all the cases studied takes place presumably through a process of 1,2-aminobromination of alkenes. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Aziridination; Chloramine-T; Lithium bromide; Olefin; Sodium metaperiodate

Novel synthesis and characterization of titanium superoxide and its application in organic oxidative processes - Reddy, R. Santhosh; Shaikh, Tanveer Mahamadali; Rawat, Varun; Karabal, Pratibha U.; Dewkar, Gajanan; Suryavanshi, Gurunath; Sudalai, Arumugam (Catalysis Surveys from Asia, 2010)
A novel, exceptionally stable titanium superoxide radical ion was prepared and its structure determined by FTIR, ESR, Raman spectroscopy, X-ray diffraction, thermogravimetric/differential thermal analysis and elemental analysis. This heterogeneous catalyst has been found to be effective for the selective oxidation of aromatic amines and phenols to the corresponding nitro aromatics and p-quinones, respectively. In addition, this non-toxic, inexpensive and reusable catalyst has also been used in aminobromination of olefins, which proceed to give the 1, 2-bromoaminated anti-Markovnikov product. A brief account of these results is summarized in this review.
Keywords: Amino Bromination; Anti-Markovnikov; heterogeneous catalyst; Oxidation; Titanium superoxide

Regiospecific azidoiodination of alkenes with sodium periodate, potassium iodide, and sodium azide: a high-yield synthesis of beta-iodoazides - Chouthaiwale, Pandurang V.; Karabal, Pratibha U.; Suryavanshi, Gurunath; Sudalai, Arumugam (Synthesis-Stuttgart, 2010)
The combination of sodium periodate, potassium iodide, and sodium azide has been found to be an efficient, simple, and inexpensive reagent system for azidoiodination of alkenes. The regiospecific 1,2-azidoiodination proceeds in an anti-Markovnikov fashion to produce beta-iodoazides in excellent yields.
Keywords: alkenes; azides; azidoiodination; beta-iodoazides; regio-specific

NaIO4-NaN3-mediated diazidation of styrenes, alkenes, benzylic alcohols, and aryl ketones - Kamble, Dayanand A.; Karabal, Pratibha U.; Chouthaiwale, Pandurang V.; Sudalai, Arumugam (Tetrahedron Letters, 2012)
Sodium periodate and sodium azide combination has been found to be an excellent reagent system suitable for the direct diazidation of styrenes, alkenes, benzylic alcohols, and aryl ketones to produce the corresponding vicinal and geminal diazides respectively in high yields under mild reaction conditions. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: alkenes; Aryl ketones; Geminal diazides; Sodium periodate; Vicinal diazides

Optically pure gamma-butyrolactones and epoxy esters via two stereocentered HKR of 3-substituted epoxy esters: a formal synthesis of (-)-paroxetine, Ro 67-8867 and (+)-eldanolide - Devalankar, Dattatray A.; Karabal, Pratibha U.; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2013)
The HKR of racemic anti- or syn-3-substituted epoxy esters catalyzed by a Co(III)salen complex provides ready access to the corresponding enantioenriched 3,4-disubstituted gamma-butyrolactones and 3-substituted epoxy esters. This strategy has been successfully employed in the formal synthesis of biologically active 3,4-disubstituted piperidine derivatives, (-)-paroxetine and Ro 67-8867 and a natural product, (+)-eldanolide.

Co(III)(salen)-catalyzed phenolic kinetic resolution of two stereocentered benzyloxy and azido epoxides: its application in the synthesis of ICI-118,551, an anti-hypertensive agent - Karabal, Pratibha U.; Kamble, Dayanand A.; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2014)
The salen Co(III)-catalyzed phenolic kinetic resolution of racemic anti- or syn-azido and benzyloxy epoxides provides a practical route to a range of enantioenriched anti-or syn-1-aryloxy-3-azido or benzyloxy-2-alcohols in excellent yields and ees. The synthetic potential of this protocol is illustrated with an enantioselective synthesis of ICI-118,551, a beta-blocker, in a highly optically pure form (99% ee).

Concise enantioselective synthesis of naturally active (S)-3-hydroxypiperidine - Dey, Soumen; Karabal, Pratibha U.; Sudalai, Arumugam (Synthetic Communications, 2015)
A short and efficient enantioselective synthesis of natural product (S)-3-hydroxypiperidine has been achieved starting from commercially available raw materials employing two catalytic routes: (i) cocatalyzed hydrolytic kinetic resolution (HKR) of racemic methyl-3-(oxiran-2-yl)propanoate; (ii) proline-catalyzed -aminooxylation followed by Horner-Wardsworth-Emmons olefination in high enantiomeric purity (97% ee) and high overall yield (38%).
Keywords: Asymmetric synthesis; bioactivity; Enantioselectivity; Natural products; organocatalysis